ЗАКОНОМІРНОСТІ ПСИХІЧНОГО УПРАВЛІННЯ ДОВІЛЬНИМИ РУХАМИ МУЗИКАНТА ПРИ ЧИТАННІ НОТ З АРКУША (Педагогіка вищої та середньої школи, 2022)
As reading musical notation and its actualization of the stave are directed by man’s psychological process, there arises the necessity to control these movements.The investigation of free movements is based on a person’s image reflection o f music he is performing and this fact makes the orientated reaction its necessary functional component. Thus, the movements resulted from the actions in terms o f their orientation are viewed at deferent levels.